Nature-based chemical sensors - Ulucan-Karnak, Fulden; Kuru-Sumer, Cansu İlke; Gedik, Fatmagul; Akgöl, Sinan (Elsevier, 2025)
The material science community has recently become very interested in nature-inspired designs, which are thought to be promising materials for the creation of high-performance chemical sensors. Their extremely dynamic interfacial interactions have opened up new possibilities for the creation of environmentally friendly, fast, sensitive, and low-cost sensing technologies. The abundance of precise hierarchical designs found in nature at the nano/microscales serve as limitless sources of inspiration for the creation of a wide variety of sophisticated materials with distinctive features. Natural chemical sensing organs with distinctive capabilities for the detection of environmental chemical signals include biological olfactory and taste systems and their transduction mechanisms. Biological functional components for chemical sensing, which are frequently taken from sensing components of biological olfactory or taste systems at the tissue level, cellular level, or molecular level, are used as a unique resource by biomimetic chemical sensors qualitatively and quantitatively. In this chapter, the most recent advances in nature-based and biomimetic chemical sensors are summarized. © 2025 Elsevier B.V., All rights reserved.
Keywords: bioinspired; biomimetics; biosensors; chemical sensors; detection; Nature-based materials